Support to the Agricultural Sector Food Security and Nutrition Strategy (2016-2025) of FMARD - CGIAR Research Program on Policies, Institutions, and Markets (2017)
The Nigeria Strategy Support Program (NSSP) provided an extensive review, support and inputs to the Federal Ministry of Agriculture and Rural Development (FMARD) in drafting and stakeholder validation of the Agricultural Sector Food Security and Nutrition Strategy (2016-2025).